PECULIARITIES OF MASTERING RUSSIAN FOLK MYTHOLOGICAL NAMES AND RITUAL TERMS IN THE KOMI-PERMYAK LANGUAGE - Иван Алексеевич Подюков (Ivan A. Podukov) (Vestnik Permskogo universiteta: Rossijskaâ i zarubežnaâ filologiâ, 2017)
The article considers how the Komi-Permyak language masters Russian (mostly dialect) vocabulary and phraseology connected with nomination of ritual realia and categories. Areas of Komi-Permyak ritual tradition characterized by the most active linguistic borrowing processes are revealed; differences in the experience of the contacting cultures is shown based on linguistic material. Ethnic peculiarities of ritual communication reflected in semantics of borrowed terms, the interference of cultural and social values of the Russian and Komi-Permyak ethnoses are examined. The analysis of mastering Russian folk cultural terms in the Komi-Permyak language is carried out at the phonetic, grammatical, lexical and semantic levels. The peculiarities of loan translation of cultural terms, linguistic interference and Russian term-production of bilingual Komi-Permyaks are described. Semantic groups of borrowed terms referring to magic, everyday, family rites (nominations of ritual attributes, characters, cultural events) are examined, functions of loanwords in the verbal ritual code (euphemization, ritual foreign-speaking) are characterized. Ethno-cultural connotation of ritual terms is revealed by means of analyzing motivation of a particular term. Borrowed terminological nominations are found to reflect transformation, creative renewal, and resemantization, on the one hand, and deformation of borrowed cultural forms, on the other hand. Similarities in the processes of mastering Russian ritual vocabulary in the Komi-Permyak language and the nature of cultural borrowing in other Finno-Ugric (Komi-Zyryan, Udmurt) languages are noted. The approaches used to study loanwords concerning spiritual culture allow us to describe the ways how borrowed ritual terms are adapted in the Komi-Permyak cultural and linguistic environment and make a conclusion about spontaneous, natural mastering of Russian folk ritual culture terminology in the Komi-Permyak language. The relevance and importance of studying the Komi-Permyak vocabulary and phraseology related to spiritual culture is emphasized in terms of linguoculturological and ethnolinguistic aspects.